Understanding mobile advertising acceptance: an integrative approach - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2015)
With over 6 billion people having a mobile phone subscription, firms use mobile marketing for various marketing oriented purposes such as delivering promotional offers and conveying personalised advertising messages, providing value generating services, facilitating word of mouth, awarding customer loyalty and collecting feedback. This study proposes a model to predict consumers' mobile advertising acceptance by relating it to various purposely selected consumer-and message-related factors. Moreover, the paper examines the empirical link between acceptance and word-of-mouth. On the basis of survey results from 353 mobile phone users, the authors test the proposed model with SEM and discuss a number of theoretical and managerial recommendations.
Keywords: mobile advertising; mobile advertising acceptance; attitude towards mobile advertising; word-of-mouth; WOM; structural equation modelling; mobile communications; WORD-OF-MOUTH; COMMERCE; TRUST; INFORMATION; DIFFUSION; ATTITUDES